A profile of poisoning in pediatric population in rural hospital in Jammu - Kumar, Niraj; Gupta, Shallini; Sharma, Sanjeev; Gupta, Vikram (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Acute poisoning is one of the commonest Pediatric emergencies and an important cause of morbidity and mortality. This study is aimed at understanding the incidence, aetiology and manner of poisoning, outcome among children less than 18 years reporting to Pediatric department at sub district Hospital level in Jammu region. Methods: All the children between one month and eighteen years of age reporting to the Pediatric Emergency of SDH Akhnoor, Jammu over a period of one year as a case of acute poisoning were included in the study. The information obtained from subjects/parents/guardians and examinations of subjects was recorded on a pretested proforma and analyzed. Results: A total of 150 patients were admitted as a case of poisoning over a study period of one year. Male: Female ratio was 1.41:1. Total incidence rate was 2.94/100 0 population over a period of one year. Majority of the cases were accidental (94.67%) while suicidal attempt cases were 5.33%. Most the cases (49.33%) were due to accidental ingestion of household products followed by drug ingestion (21.33%), food poisoning (14%) and then agricultural/industrial products (8%). Maximum patients (86.6%) recovered while 2% referred to higher centre and rest 11.3% either absconded or lost to follow up. Conclusions: Acute poisoning in children is usually accidental with favourable outcome. Death can happen depending upon nature of poison and the stage at which the patient is brought to the hospital. Poisoning can be prevented by increasing public awareness, counselling and right guidance to the parents.